2002
DOI: 10.1161/01.cir.0000035247.42888.82
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Statin Therapy in Children With Familial Hypercholesterolemia

Abstract: for the Simvastatin in Children Study GroupBackground-A multicenter, randomized, double-blind, placebo-controlled study was conducted to evaluate LDL cholesterol-lowering efficacy, overall safety, and tolerability and the influence on growth and pubertal development of simvastatin in a large cohort of boys and girls with heterozygous familial hypercholesterolemia (heFH). Methods and Results-A total of 173 heFH children (98 boys and 75 girls) were included in this study. After a 4-week diet/placebo run-in perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
2
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(157 citation statements)
references
References 28 publications
4
144
2
5
Order By: Relevance
“…In this context, statin therapy was shown to restore endothelial function in children with familial hypercholesterolemia 56 and has also demonstrated to be safe. 57 In conclusion, our cross-sectional data demonstrate that obese children have elevated blood levels of the inflammation markers hsCRP and hsIL-6 and of E-selectin, a specific endothelial activation marker. 58 These are markedly increased at a BMI Ն40 kg/m 2 .…”
Section: Discussionmentioning
confidence: 59%
“…In this context, statin therapy was shown to restore endothelial function in children with familial hypercholesterolemia 56 and has also demonstrated to be safe. 57 In conclusion, our cross-sectional data demonstrate that obese children have elevated blood levels of the inflammation markers hsCRP and hsIL-6 and of E-selectin, a specific endothelial activation marker. 58 These are markedly increased at a BMI Ն40 kg/m 2 .…”
Section: Discussionmentioning
confidence: 59%
“…The introduction of bile acid sequestrants in tablet form may improve adherence. Short-term trials of HMG-CoA reductase inhibitors in youth have confirmed their safety and efficacy (168,169) in youth with familial hypercholesterolemia. These agents are approved for use in children Ն10 years of age with familial hypercholesterolemia.…”
Section: Type 1 Diabetes In Children and Adolescentsmentioning
confidence: 98%
“…In each trial, the agent was specifically studied in familial hypercholesterolemia, using an established surrogate outcome (changes in lipid profiles). Impressively, all 8 studies led to efficacy‐related labeling changes 21, 22, 23, 24, 25, 26, 27, 28. The use of a specific patient population with markedly abnormal lipid profiles has been identified as a critical feature in the success of these trials.…”
Section: Approaches To Improving Clinical Trials In Children With Carmentioning
confidence: 99%
“…Successful trials conducted under the regulatory incentive provisions have been primarily related to pediatric hypertension11, 12, 13, 14, 15, 16, 17, 18, 19, 20 and familial hypercholesterolemia 21, 22, 23, 24, 25, 26, 27, 28. Although these trials led to important changes for these particular diseases, they faced challenges related to patient recruitment, disease heterogeneity, dosing, endpoint selection, and, in general, an overall lack of experience in conducting randomized clinical trials in children.…”
mentioning
confidence: 99%